The effect of a reader’s theater on preschool children’s reading fluency and comprehension - Isa, Zainiah Mohamed; Luen, Loy Chee; Sewestian, Agnes Vimala; Omar, Ainon (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Previous studies revealed that Readers Theater instruction has improved fluency and comprehension skills of kindergarten children. In this study Reader’s Theater has been implemented to investigate its effectiveness towards improving fluency and comprehension skills of kindergarten children in Malaysia. Using quasi- experimental research design and qualitative methods, data was collected from 50 kindergarten children in the District of Batang Padang, Perak. The experimental study was carried out for six weeks where the control group was given the passage of the story, while the treatment group received Readers Theater scripts of the same story. Test statistics indicated significant differences between the treatment and control groups; Z = -3.00, p .05 in comprehension skills. It can therefore be concluded that Readers Theater instruction is beneficial to increase fluency skill for the kindergarten children in Malaysia and thus recommended as part of literacy enhancement in the kindergarten classroom.